METABOLIC HEALTH AND ITS DETERMINANTS IN IRAQI UNIVERSITY STUDENTS: A CROSS-SECTIONAL ANALYSIS - Noor Nayyef Oddah (European Science Publishing, 2026)
Background: Metabolic syndrome (MetS) is a clustering of cardiometabolic risk factors that substantially increases the risk of cardiovascular disease and type 2 diabetes mellitus. Although traditionally associated with older populations, recent evidence suggests a rising burden of MetS among young adults, particularly in regions undergoing rapid lifestyle transitions. Objective: This study aimed to assess the prevalence of metabolic syndrome and its associated metabolic and lifestyle-related risk factors among university students in Diyala Province, Iraq. Methods: A cross-sectional survey of university students was performed. Anthropometric measurements, blood pressure and biochemical (fasting blood glucose and lipid profile) parameters were determined. MetS was diagnosed according to accepted criteria. Frequency of consumption of fast-food was assessed as lifestyle factor. Comparisons between students with and without MetS were conducted statistically. Results: Metabolic syndrome was identified among university students, indicating the presence of early cardiometabolic risk, suggesting an early cardiometabolic risk profile. The body mass index, waist circumference, blood pressure, fasting blood glucose levels, triglycerides, low density lipoprotein-cholesterol (LDL-C), and VLDL were significantly higher and high-density lipoprotein cholesterol (HDL-C) lower in those with MetS compared to their healthy counterparts. More frequent consumption of fast food (>3 times/week) was related with worse metabolic profiles: higher glucose, dyslipidemia, central obesity and heavier blood pressure. Conclusions: Metabolic syndrome and its components exist and are present in university students, in Diyala Province suggesting early occurrence of cardiometabolic risk. Frequent indulgence in fast-food is an important modifiable.